Bank Competition and Firm Creation - Dell'Ariccia, Giovanni (Washington, D.C. : International Monetary Fund, 2001)
This paper investigates the empirical relationship between competition in the financial sector and the creation of firms in the non-financial sector. It finds that bank competition has an overall positive effect on firm creation. However, consistent with theories of banking arguing that competition may reduce the availability of credit to informationally opaque firms, it also finds that asymmetric information limits the overall positive effect of bank competition on firm creation. Indeed, bank competition is less favorable to the emergence of new firms in industrial sectors where informational asymmetries are more important, and in extreme cases has a negative effect.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet